Rubella Infection In Pregnancy - Joserizal Serudji (Universitas Andalas, 2022)
Rubella is a systemic viral disease that is mild, non-specific, rarely diagnosed, and easily transmitted. Rubella virus easily crosses the placenta, so infection in pregnancy, especially in the first trimester, has the risk of transmitting to the fetus and potentially causing abortion, fetal death, and congenital rubella syndrome (CRS). CRS includes auditory, sensorineural, cardiac, and ocular abnormalities, and is an irreversible congenital disorder. Rubella can be prevented by the administration of antirubella vaccination.Serology tests are still the most reliable diagnostic test today, although these immune reactions appear later than the appearance of the rash. Analysis of serology test results can provide information on whether you are in acute infection, infected, and are still active, or chronic infection and are currently active or inactive.Management of rubella infection in pregnancy is symptomatic, nothing can be done for CRS in pregnancy. Postpartum CRS management is multidisciplinary and supportive